The potential for gastro-tourism in China: A Case Study of Beijing - Deng, K (2010)
Recently, tourism industry is becoming more and more popular for scholars. However, the analysis of the food tourism literature and the promotional material of various destinations indicate that the role of food in the marketing of destinations has until recently received very little attention locally and globally. Whereas, all indications shows that the local food holds much potential to enhance sustainability in tourism; contribute to the authenticity of the destination; strengthen the local economy; and provide for the environmentally friendly infrastructure.